O processo de (re)produção do espaço urbano de Nova Parnamirim - Souza, Francisco Eloi de (2006)
The public and private politics that was implemented in Natal, have always been attracting, great contingent of people in search of employments. However, not always, they can attend the migratory demands. Recently, Nova Parnamirim that is situated in the municipal district of Parnamirim - RN, due to proximity with Natal, it is passing for an intensive and accelerated occupation process impelled by the urban politics that created and they determined new diversities, leaning in the growth of the modern tertiary. In this context, Nova Parnamirim is suffering, along the time, substantial transformations in your espace, so much of nature social as environmental, that are affecting in the quality of your residents' life. This fact is mainly linked in the absence of an appropriate urban planning that have to be considered as an instrument norteador of the development of the city in its constant construction process. The study has as objective to analyze the social-space dynamics of the area and their implications, identifying the principal agents that promote and they benefit of that urbanization process. For the ccomplishment of this research it was executed bibliographical readings that turn of theoretical studies about the urban subjects and enviroments, besides field activities for the rising of the data investigated in the methodological approach